Advances in the diagnosis and treatment of viral hepatitis B and C in China - Jia, Jidong (Chinese medical journal, 2022)
[16] The proportion of entecavir (ETV) and tenofovir disoproxil fumarate (TDF) in the prescribed antiviral agents had increased from 13.5% in 2003 to 79.7% in 2016 as shown by an analysis of the China Registry of Hepatitis B.[18] In 2019, the price of generic ETV and TDF has reduced by 90%, and the price of propriety ETV, TDF, and tenofovir alafenamide fumarate has also dramatically reduced. After massive price reduction through governmental negotiation, all of these highly efficacious DAAs have been included in the reimbursement list of the basic social health insurance. According to estimates, in China, only around 25% of all HBV and 30% of all HCV cases were actually diagnosed, and 17% of CHB and 9% of CHC patients eligible for treatment were actually treated. [2] Studies suggested that scaling up of the test-and-treat strategy could dramatically reduce HBV- or HCV-associated mortality, which is cost-effective or even cost-saving. [...]continuous efforts to improve the awareness of HBV and HCV and resource allocation on their prevention, test, and treatment are still needed to eliminate viral hepatitis as a public health threat by 2030.